Integrating Creative-Based Learning into the Active Learning Process to Enhance Creative Thinking Skills in Computer Information Courses - Poolsombat, Phapawee; Laisuwannachart, Panjarut; Phuphaniat, Marut (International Journal of Educational Communications and Technology, 2025)
Integrating Creative-Based Learning into the Active Learning Process to Enhance Creative Thinking Skills in Computer and Information Technology Courses refers to an instructional approach that integrates in-class learning with online learning activities. This model emphasizes active learning as the core strategy to foster student engagement and develop creative thinking skills. Furthermore, it incorporates the application of technology as an integral component, particularly in the context of public health, to ensure alignment with modern and emerging technological advancements. The objectives of this research were: (1) to design a blended Creative-Based active learning model that enhances learners’ creative thinking skills in computer and information technology courses, and (2) to evaluate the effectiveness of the proposed model. The findings revealed that the design, which blends creative-based active learning management processes, was highly appropriate for enhancing creative thinking skills, with an overall high level of suitability (M = 4.56, SD = 0.44). Based on these results, it can be concluded that this instructional model is suitable for practical implementation, offering flexibility in learning, and effectively supporting continuous and lifelong learning.